UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI MENGGUNAKAN METODE LEARNING CONTRACT PADA SISWA KELAS X SMK YADIKA NATAR LAMPUNG SELATAN - Fitria, Nur (LPPM STKIP PGRI Bandar Lampung, 2018)
The improving result economic studies learning through cooperative model Learning Contract in X grade student of Vocational High School Yadika Natar. The purpose of this research was to improve the economic learning through cooperative model Learning Contract type in X grade SMK Yadika Natar Lampung Selatan. This research uses classroom action research techniques. The research was conducted in two cycles. Subject of this study is the X grade student of vocational high school Yadika Natar. Which has 30 student. Data sources come from teachers, students dan researchers. Data collection techniques using observation, testing, interview, and documentations. The validity of data using triangulation methods technique and other sources. Analysis of the data used by the qualitative and quantitative analysis. The result show that the use of cooperative learning â€œLearning Contractâ€ can improve the economic studies learning.